Understanding the Role of Automation in Society and its Impact on Labour Market - Muhammad Touseef; Saira Siddiqui; Nabeela Farah (PT FORMOSA CENDEKIA GLOBAL, 2023)
Automation is the procedure of operating technology to manage and operate tasks, machines, and processes without the need for human input. It employs control systems and advanced technology to enable self-sufficiency in the functioning these systems. We have conducted this study to examine the effects and ramifications of automation on contemporary society, considering its impact on productivity, employment, morality, and economic and social development. It provides an overview of the current state of automation and its potential impact on society. Our study has found that automation has positive and negative consequences for society, including a decline in the job market and a change in the skills set for employment. It was a comprehensive qualitative study that included a literature review, 16 online interviews with experts from 16 countries, and online surveys. We categorized the findings by analyzing the data using thematic analysis. Our results suggest that there should be laws and regulations on the use of automation in society to minimize its adverse impacts on society. This study suggests that automation should improve the quality of life and create more opportunities for people in the market